Transaction Management: Value Creation by Reducing Transaction Costs - Frank A.G. den Butter (Tinbergen Institute, 2010)
In this era of globalization we see an increase in specialization: the production chain issplit up in more and more parts and the production of these parts is outsourced to thoseplaces in the world where production is relatively cheapest and most efficient. Itimplies that transaction costs, associated with the coordination of production and tradein parts and components, become increasingly important. In small open service orientedeconomies like the Netherlands, transaction costs may amount to up to 50% of totalvalue added. Therefore, the ability and skill to keep transaction costs low is vital for thecompetitive position of a firm or country. This is what transaction management is about:create value from these transactions by keeping transaction costs as low as possible.Transaction management is based on modern theories of transaction costs economics,institutional economics, industrial organization and international trade. It makes thesetheories operational for strategic decision making in industry and government. Thischapter surveys how transaction management as a practical tool for the organization ofproduction has been inspired by these modern economic theories.
Keywords: D23; F2; F43; L23; 330; transaction costs; outsourcing; trade in tasks; fragmentation of production; make or buy decision; game of trust; Outsourcing; Transaktionskosten; Produktionsplanung; Make-or- Buy-Entscheidung; Niederlande